Release Strategies of Silver Ions from Materials for Bacterial Killing - Xu, Zhiwen; Zhang, Cai; Wang, Xiang; Liu, Dingbin (ACS applied bio materials, 2021)
Silver-based antibacterial agents have attracted much attention in biomedical fields owing to their high antibacterial activity. Silver ions (Ag+) play a significant role in killing bacteria because they can readily adsorb to most biomolecules (DNA, membrane protein, enzymes, or intracellular cofactors) in bacteria to inactivate their functions. In this review, recent advances in the ways of Ag+ release from silver-contained materials were discussed. As a start, the antibacterial mechanisms of Ag+ was summarized. Then, the release strategies of Ag+ from silver-carrying materials have been categorized into two types: (1) passive release and (2) stimuli-responsive release. In particular, the stimuli-responsive materials relying on either endogenous or exogenous stimuli have been rationally designed for eliminating bacteria with high efficacy and selectivity. Future studies should focus on enhancing the controllability of Ag+ release in the infected sites of the human organs.